Incontinentia Pigmenti: A Case Report of Early Clinical Symptoms in a Lack of Family Inheritance Positive Result - Yuan F; Zhu FN; Liu XJ; Li J; Xu HT (Dove Medical Press, 2023)
Fang Yuan,1,* Feng-Na Zhu,2,* Xiao-Juan Liu,1,* Jun Li,3 Hong-Tao Xu1 1Department of Pediatrics, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China; 2Department of Neonatology, Maternal and Child Health Hospital of Hubei Province, Wuhan, 430070, People's Republic of China; 3Department of Blood Purification, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China*These authors contributed equally to this workCorrespondence: Jun Li; Hong-Tao Xu, General Hospital of Central Theater Command of the People's Liberation Army, 627#, Wuluo Road, Wuchang District, Wuhan, Hubei Province, 430070, People's Republic of China, Tel +86-13659846692, Fax +86-27-50773333, Email lijun15261@163.com; xuht5409@163.comBackground: Incontinentia pigmenti (IP), also known as Bloch-Sulzberger syndrome, is an X-linked dominant genetic disease involving multiple systems. Previous literature has not reported the case of parents with negative genetic test results, and typical early clinical symptoms and auxiliary inspection results were also lacking.Case Report: A female child was found to have broken skin immediately after birth with no family inheritance disease, and the area of the broken skin increased. Immediately afterward, Head magnetic resonance imaging (MRI) showed multiple blood lesions in the brain. Then, the wide-angle digital retinal imaging system suggesting that fundus fluorescein angiography showed fundus vascular loop-like changes. And blood genetic testing showed that exons 4- 10 of the NEMO gene located in Xq28 were deleted. The patient was eventually diagnosed with IP. However, her parents were a non-consanguineous healthy couple, with no specific skin, oral, or perineal diseases. And her parents' blood genetic testing showed that the parents and sisters of the patient did not have the NEMO gene exon deletion of Xq28.Conclusion: This case demonstrates the process from suspected neonatal IP cases without familial inheritance to diagnosis, which showed the typical early clinical symptoms and auxiliary inspection results. This case showed that the parents of patients with IP do not necessarily have clinical symptoms and positive symptoms of genetic testing results.Keywords: incontinentia pigment, genodermatosis, Bloch-Sulzberger syndrome, skin disease, NEMO gene